Investigation of Psychosoial Symptoms of Children in Hospital in Terms of Children's Variables - Merve SELBES; Gülay MANAV; Gonca KARAYAGIZ MUSLU (Atatürk University, 2021)
Aim: This research was conducted to examine the psychosocial symptoms of children aged 6-12 who were hospitalized in the pediatric and pediatric surgical services of a University Hospital. Method: June-July 2019, 50 children in the 6-12 age group who had been in bed at a University Hospital for less than three days, diagnosed with an acute or chronic disease, admitted to participate in the study. "Personal Information Form" and "psychosocial symptoms diagnostic scale for hospitalized children" were used to collect the data. The data were evaluated in the SPSS program and found to have no normal distribution based on Skewness, kurtosis values and Shapiro-wilk results. According to these results, the data were used for descriptive analyses, Mann Whitney U test and Kruskal Wallis analysis. Results: 54% of the children with a mean age of 8.922.23 were girls and 46% were between 10-12 years of age. The scale used in the study has five sub-dimensions: anxiety, despair, communication difficulties, anger-aggression, and regression. A significant association was observed when the relationship between anxiety and sex, anger and aggression with hospitalization experience and regression with the duration of the disease was examined. Conclusions: According to the results of the study, factors that cause the appearance of psychosocial symptoms in the child were observed. In our study, the importance of psychosocial evaluation of children receiving inpatient treatment is emphasized.